Leptin in corneas from keratoconus and infectious keratitis patients - Aydemir, O; Naziroglu, M; Çolakoglu, N; Yilmaz, T; Kükner, A; Kükner, AS (Mary Ann Liebert, Inc, 2005)
Purpose: Leptin is produced primarily by adipose tissue. More recent studies have shown extra sites of leptin production in physiologic and ill human tissues. However, whether leptin originates from human corneas in infectious keratitis and keratoconus is not known. The aim of this study was to demonstrate and quantitate leptin expression in corneas with infectious keratitis and keratoconus and make comparisons to control corneas. Methods: We examined the immunohistochemical staining of leptin in nine corneas surgically excised from patients with infectious keratitis (3 patients), keratoconus (3 patients), and donor corneas (3 patients). Results: The results were analyzed using a semi quantitative scoring system of mild, moderate, and strong. Cells of the infectious keratitis group had the strongest leptin staining intensity, the control group had moderate, and the keratoconus group had mild staining intensity. The more vascular corneas in the infectious keratitis group were also associated with the greatest leptin staining. Conclusions: Our findings indicate that leptin expression was present in all three sources of corneas (infectious keratitis, keratoconus, and normal control). Quantitative scoring would imply it may play a role in infectious keratitis, although further experiments are necessary to establish any causal relationship.
Keywords: Diabetic-Retinopathy; Growth-Factor; Expression; Angiogenesis; Cloning; Gene